318 Olaparib plus pembrolizumab in patients with previously treated advanced solid tumors with homologous recombination repair mutation and/or homologous recombination repair deficiency: KEYLYNK-007. (10th December 2020) - Yap, Timothy A; Dhawan, Mallika; Hendifar, Andrew E; Maio, Michele; Owonikoko, Taofeek K; Quintela-Fandino, Miguel; Shapira-Frommer, Ronnie; Saraf, Sanatan; Qiu, Ping; Jin, Fan; Gozman, Alexander; Levine, Douglas A
Abstract : Background: Treatment with the anti–PD-1 antibody pembrolizumab has improved clinical outcomes in multiple previously treated advanced solid tumors. The poly (ADP-ribose) polymerase (PARP) inhibitor olaparib has shown antitumor activity as monotherapy in patients with previously treated advanced ovarian, breast, pancreatic, and prostate cancers with BRCA1/BRCA2 mutations (BRCAm). Activity was also seen in patients with previously treated advanced solid tumors with other homologous recombination repair mutation (HRRm) and in those with ovarian cancer with homologous recombination repair deficiency (HRD) phenotype. PARP inhibitors have been found to increase interferon signaling and tumor infiltrating lymphocytes, enhancing tumor susceptibility to immune checkpoint blockade. Antitumor activity of PD-(L)1 plus PARP inhibition was found to be higher than expected with either agent alone in patients with recurrent ovarian cancer regardless of BRCAm or HRD status and in patients with BRCAm breast cancer. KEYLYNK-007 (NCT04123366 ) evaluates the antitumor activity and safety of olaparib in combination with pembrolizumab in patients with previously treated advanced solid tumors with HRRm and/or HRD. Methods: This phase 2, nonrandomized, multicenter, open-label study will enroll approximately 300 patients aged ≥18 years with histologically/cytologically confirmed, previously treated, advanced solid tumors with HRRm and/or HRD per Lynparza HRR-HRD assay (Foundation Medicine, Inc., Cambridge, MA, USA), with an ECOG PS of 0-1. Patients will be grouped by biomarker status: subgroup 1: BRCAm; subgroup 2: HRRm without BRCAm; and subgroup 3: HRD positive without HRRm (loss of heterozygosity score ≥16 per Lynparza HRR-HRD assay). Patients will receive olaparib 300 mg twice daily + pembrolizumab 200 mg intravenously Q3W (35 cycles) until PD, unacceptable AEs, intercurrent illness, investigator decision, withdrawal of consent, or pregnancy. Tumor imaging assessment by blinded independent central review (BICR) per RECIST v1.1 or Prostate Cancer Working Group (PCWG)–modified RECIST v1.1 for prostate cancer will occur Q9W for 12 months, then Q12W until PD, start of new anticancer treatment, withdrawal of consent, pregnancy, or death. AEs will be monitored throughout the study and for 30 days after final dose (90 days for serious AEs). The primary endpoint is ORR (RECIST v1.1 or PCWG–modified RECIST version 1.1 by BICR). Secondary endpoints include duration of response (DOR) and PFS (RECIST v1.1 or PCWG–modified RECIST v1.1 by BICR), OS, and safety. Point estimate and exact Clopper-Pearson CI for ORR, and Kaplan-Meier estimates for DOR, PFS, and OS will be calculated. A total of 89 sites are currently enrolling in 20 countries. Results: N/A Conclusions: N/A Trial Registration: ClinicalTrials. gov identifier, NCT04123366 Ethics Approval: An independent institutional review board or ethics committee approved the protocol at each study site, and the trial is being conducted in compliance with Good Clinical Practice guidelines and the Declaration of Helsinki.